A roch wind blawin': Frank Bechhofer, the disruptive intellectual. Issue 3 (August 2019) - Anderson, Michael; McCrone, David; Paterson, Lindsay
Abstract : Frank Bechhofer (1935–2018) made a remarkable contribution to sociology and the wider social sciences as a researcher, a teacher, and a writer. In this article three of his academic collaborators sketch out several areas in which he enriched intellectual life in Scotland.